PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. RATU POLA BUMI BANDAR LAMPUNG TAHUN 2013 - Novita, Dwi Indria (Jurnal Manajemen Magister Darmajaya, 2015)
PT. Ratu Pola Bumi is one of concrete electrical standard and concrete pole with pre-tensile system, the first in Indonesia. PT Ratu Pola Bumi has a factory located in Bandar Lampung âLampung. In order to increase the employees performance, PT Ratu Pola Bumi encourage the employees to develop themselves and do the best to upgrade their competencies, and also be discipline, so that corporation goal can be reach. Problem faced in this research is lowness of employeesâ performance, competencies that unsuitable, and indiscipline. Those problems are interdependently of each other, and suspected that performance lowness is an effect of unsuitable competency and indiscipline. The main problem of this research is how competency and discipline affect performance in PT Ratu Pola Bumi. This research aims to find out the effect of competency and discipline on employeesâ performance in PT Ratu Pola Bumi. Research data is collected using questionnaire and literature, while analysis using double linear regression. The collected data is processed by SPSS for Windows version 17.00. This research uses 150 respondents. The result of this research shows that competency (X1), and disciplines (X2) have positive effect on employeesâ performance (Y) in PT Ratu Pola Bumi.Keywords: Competency, Discipline, Employeesâ Performance